Geochemical constraints on the origin of the Annieopsquotch ophiolite belt, Newfoundland Appalachians - Lissenberg, Cornelis Johan; van Staal, Cees R.; Bédard, Jean H.; Zagorevski, Alexandre (Geological Society of America Bulletin, 2005)
The Early Ordovician Annieopsquotch ophiolite belt occurs immediately west of the main Iapetus suture zone, and imposes important constraints on the tectonic processes associated with closure of the peri-Laurentian portion of Iapetus. The Annieopsquotch ophiolite, the most prominent ophiolite within the Annieopsquotch ophiolite belt, exposes a 5.5-km-thick section of gabbros, sheeted dikes, and pillow basalts, in which three magmatic episodes have been recognized based on field and geochemical data. The first phase is composed of layered troctolites, which are preserved as enclaves within the gabbro zone. Trace element modeling suggests the troctolites crystallized from boninitic melts. The troctolite substrate was intruded by the dominant, second, tholeiitic magmatic phase, which formed a gabbro-sheeted dike-basalt sequence. All tholeiites have suprasubduction zone chemical characteristics, but the suprasubduction zone signature decreases toward the top of the basalt sequence. The third magmatic episode is composed of primitive dikes, which are interpreted as off-axis intrusions. Other ophiolites within the Annieopsquotch ophiolite belt have comparable geochemical signatures, suggesting they may have constituted a single piece of oceanic lithosphere. Based on geochemical and regional tectonic constraints, the Annieopsquotch ophiolite belt is interpreted to have formed during initiation of west-directed subduction. Fast rollback of the subducting slab would have induced volatile-fluxed decompression melting of previously depleted mantle, yielding boninitic melts. The suprasubduction zone tholeiite sequence would have formed from ascending fertile mantle fluxed with sub-duction-related fluids as rollback continued. This suggests that the Annieopsquotch ophiolite belt does not represent the remnants of normal oceanic crust or backarc basin crust, as previously thought. Our model constrains the initiation and early evolution of a west-dipping peri-Laurentian subduction zone that was responsible for formation of ...